2021
DOI: 10.1016/j.apsb.2021.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Environmental toxicant-induced maladaptive mitochondrial changes: A potential unifying mechanism in fatty liver disease?

Abstract: Occupational and environmental exposures to industrial chemicals are well known to cause hepatotoxicity and liver injury. However, despite extensive evidence showing that exposure can lead to disease, current research approaches and regulatory policies fail to address the possibility that subtle changes caused by low level exposure to chemicals may also enhance preexisting conditions. In recent years, the conceptual understanding of the contribution of environmental chemicals to liver disease has progressed si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 147 publications
0
8
0
Order By: Relevance
“…The adverse effects of VOCs have been seen even at low levels of exposure in several epidemiological studies. Studies have shown that diseases such as sensory irritation and respiratory symptoms, organ damage, nervous system defects, autoimmune diseases, and cancer are linked with a substantial exposure to VOCs which enter the human body through different ways such as inhalation, ingestion, and skin absorption to cause pathologies (13,20,138). Diseases linked with VOC exposure include pulmonary diseases, immunological system disorders, acute myeloid leukemia in children, skin diseases, and rheumatoid arthritis (20,139,140).…”
Section: Volatile Organic Compound Exposure and Health Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The adverse effects of VOCs have been seen even at low levels of exposure in several epidemiological studies. Studies have shown that diseases such as sensory irritation and respiratory symptoms, organ damage, nervous system defects, autoimmune diseases, and cancer are linked with a substantial exposure to VOCs which enter the human body through different ways such as inhalation, ingestion, and skin absorption to cause pathologies (13,20,138). Diseases linked with VOC exposure include pulmonary diseases, immunological system disorders, acute myeloid leukemia in children, skin diseases, and rheumatoid arthritis (20,139,140).…”
Section: Volatile Organic Compound Exposure and Health Defectsmentioning
confidence: 99%
“…Additionally, they have a high potential risk for human exposure (146) and are associated with liver and kidney damage as well as cardiovascular diseases (147). Reactive metabolites in VOCs such as aldehydes cause oxidation and protein carbonylation, which is the root of most modified protein and downstream dysfunctions that damage organelles such as the mitochondrion and cause cell damage and bioenergetic dysfunction leading to organ damage (138). A high-level exposure to VOCs shows hepatotoxicity in humans and promotes underlying injuries to liver function, thus causing liver damage and failure in severe cases.…”
Section: Vocs and Organ Dysfunction And Diseasesmentioning
confidence: 99%
“…A noteworthy observation demonstrated that insulin-resistant geriatric patients have significantly high triglyceride concentrations in both the skeletal muscle and liver cells ( 25 ). This implies that insulin resistance might arise due to defects in fatty acid oxidation in the mitochondria.…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%
“…This finding is in-line with previous work showing that VC exposure alters metabolism in precancerous models. [32,36,46] Although altered metabolism is an established key factor in the development of CLD, more recent work has identified that it also may contribute to cancer biology and the development of HCC. [47][48][49][50][51] Moreover, ChREBP activation has been previously shown to promote HCC proliferation and has been associated with poor outcome in patients with HCC.…”
Section: The Enhancement Of Hcc By Vc Exposure Leads To a Unique Epit...mentioning
confidence: 99%